Nicotinamide adenine dinucleotide and the sirtuins caution: Pro-cancer functions - Palmer, R.D.; Vaccarezza, Mauro (2021)
This scoping review aims to perform a brief but comprehensive assessment of existing peer-reviewed literature and determine whether raising nicotinamide adenine dinucleotide can prevent or promote tumorigenesis. The examination of extensive peer-reviewed data regarding the synthesis of nicotinamide adenine dinucleotide has been performed with a focus on nuclear dynamics and the deoxyribose nucleic acid repair pathway. Various enzymatic protective functions have been identified from nicotinamide adenine dinucleotide levels, as well as the threat role that is also explored. Nicotinamide adenine dinucleotide precursors and sirtuin-activating compounds are becoming ubiquitous in the commercial market. Further research into whether elevating levels of nicotinamide adenine dinucleotide or overexpression of sirtuins can increase the potential for neoplasm or other age-related pathophysiology is warranted due to the high energy requirements of certain diseases such as cancer.